Initial Training of New Platforms on Climate Change - Climate-Smart Agriculture - Positioning of Multistakeholder Platforms within the AICCRA System - Sidibe, Mahamadou (2024)
This report summarizes the initial training of two newly established multi-stakeholder platforms under the Accelerating Impacts of CGIAR Climate Research for Africa (AICCRA) project, in partnership with AfricaRice and the Office du Niger. The training aimed to enhance the capacity of the Synergie des Exploitants Agricoles de l’Office du Niger (SEXAGON) and the Collective of Women Farmers of the Office du Niger (CFEON) to disseminate climate-resilient and nature-positive solutions.